The Growing and Glowing Toolbox of Fluorescent and Photoactive Proteins. Issue 2 (February 2017) - Rodriguez, Erik A.; Campbell, Robert E.; Lin, John Y.; Lin, Michael Z.; Miyawaki, Atsushi; Palmer, Amy E.; Shu, Xiaokun; Zhang, Jin; Tsien, Roger Y.
Abstract : Over the past 20 years, protein engineering has been extensively used to improve and modify the fundamental properties of fluorescent proteins (FPs) with the goal of adapting them for a fantastic range of applications. FPs have been modified by a combination of rational design, structure-based mutagenesis, and countless cycles of directed evolution (gene diversification followed by selection of clones with desired properties) that have collectively pushed the properties to photophysical and biochemical extremes. In this review, we provide both a summary of the progress that has been made during the past two decades, and a broad overview of the current state of FP development and applications in mammalian systems. Trends: Monomeric red and far-red FPs and indicators now perform nearly as well as the best green FPs (and indicators). Reversible and irreversible photochromism in FPs can be exploited to increase optical resolution and improve contrast compared with traditional fluorescence microscopy. Infrared FPs (IFPs) are becoming ever more useful as labels for various proteins that allow correct localization and whole-animal imaging. IFPs can serve as an additional fluorescent 'color' for simultaneous imaging with visible FP-labeled proteins. Bacterial phytochrome (BphP)-based IFPs provide a new scaffold for engineering fluorogenic indicators, which are ideal to visualize spatiotemporal dynamics of cell signaling in vivo . Small ultra-red FP (smURFP) is the brightest far-red nonprototypical FP (comparable with EGFP) and is extremely photostable. smURFP may prove particularly useful as a photostable FP for super-resolution imaging and as a FRET acceptor for biosensing applications. The engineering of new fluorescent indicators that combine features of prototypical FP-based indicators with photochromic proteins can reveal the cellular maps of biochemical activities in super-resolution. FPs can be used as optogenetic actuators to manipulate cellular and protein functions through chromophore-assisted light inactivation or light-controlled protein oligomerization.